Identification of P-glycoprotein co-fractionating proteins and specific binding partners in rat brain microvessels - Tome, Margaret E. (J Neurochem, 2015)
Drug delivery to the brain for the treatment of pathologies with a CNS component is a significant clinical challenge. P-glycoprotein (PgP), a drug efflux pump in the endothelial cell membrane, is a major factor in preventing therapeutics from crossing the blood-brain barrier (BBB). Identifying PgP regulatory mechanisms is key to developing agents to modulate PgP activity. Previously, we found that PgP trafficking was altered concomitant with increased PgP activity and disassembly of high molecular weight PgP-containing complexes during acute peripheral inflammatory pain. These data suggest that PgP activity is post-translationally regulated at the BBB. The goal of the current study was to identify proteins that co-localize with PgP in rat brain microvessel endothelial cell membrane microdomains and use the data to suggest potential regulatory mechanisms. Using new density gradients of microvessel homogenates, we identified two unique pools (1,2) of PgP in membrane fractions. Caveolar constituents, caveolin1, cavin1 and cavin2, co-localized with PgP in these fractions indicating the two pools contained caveolae. A chaperone (Hsc71), protein disulfide isomerase and endosomal/lysosomal sorting proteins (Rab5, Rab11a) also co-fractionated with PgP in the gradients. These data suggest signaling pathways with a potential role in post-translational regulation of PgP activity at the BBB.